C-reactive protein and diabetic foot ulcer infections: A meta-analysis. Issue 3 (August 2022) - Zhang, Wan-Qing; Tang, Wen; Hu, Shi-Qi; Fu, Xue-Lei; Wu, Hua; Shen, Wang-Qin; Chen, Hong-Lin
Abstract: Background: Accurate identification of diabetic foot ulcer infection (IDFU) through inflammatory markers is still a challenge in clinical practice. Objectives: This meta-analysis aims to investigates whether there is a significant indigenous association between CRP level and diabetic foot ulcer infection. Methods: The studies on the diagnosis of IDFU by inflammatory marker C-reactive protein published before November 2021 in PubMed, Web of Science, Embase, and Cochrane Library were searched. Since the included seven studies were cohort studies and cross-sectional studies, the quality evaluation was founded on the standard of Newcastle-Ottawa Scale (NOS), which was convenient and straightforward. The stata 15.0 software (Cambridge, UK) was used for statistical analysis of data collected for analysis. Results: Finally, we included seven articles and investigated 592 patients, including 362 patients with IDFU and 230 patients without diabetic foot ulcer infection (NIDFU). Seven studies assessed the results of CRP, with significant heterogeneity among included studies (χ 2  = 18.93, P = 0.004; I 2  = 68.3%). Therefore, the combined effect adopts the random effect model, and the combined impact of standardized mean difference is 0.81 (95% CI 0.49–1.12; z = 4.99, p = 0.000). The funnel plot showed no significant asymmetry, and Egger's Test (z = 0.30, P = 0.764) and Begg's Test (t = −0.50, p = 0.637) showed no publication bias. Sensitivity analysis shows that the results are robust. Through subgroup analysis, we find that regional and CRP types are both sources of high heterogeneity. Meanwhile, the meta-regression results of the random effect model showed that HbA1c (P = 0.021), BMI (P = 0.029), and creatinine levels (P = 0.003) had significant effects on the heterogeneity of the relationship between IDFU, and serum CRP levels. Discussion: Meta-analysis showed a clear association between C-reactive protein and IDFU. Understanding the pathophysiology of IDFU and rapid identification of risk factors for reducing patient burdens, amputation, and mortality are essential. Highlights: CRP is a rapidly rising protein in the body's plasma when infected. CRP level was significantly associated with diabetic foot ulcer infection. CRP is a promising biomarker for the diagnosis of diabetic foot ulcer infection.